2017
DOI: 10.1016/j.sapharm.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and attributes of pharmacists in relation to practice change – A scoping review and discussion

Abstract: 3Background: Multiple barriers and facilitators to the uptake of cognitive services in pharmacy practice 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 128 publications
2
45
1
Order By: Relevance
“…Reported behaviours related to managing patients and appropriate referral (secondary outcomes) further suggest ways that community pharmacy can improve access to treatment that extends beyond existing commissioned pharmacy‐based services such as minor ailments schemes. However, situational factors including work overload, conflicting workloads, lack of equipment and concerns over insurance were cited as barriers to transfer of training suggesting practice setting characteristics remain an obstacle to implementing behaviour change, confirming previously reported findings that a lack of perceived behavioural control / ability to engage in a behaviour in a practice environment may prevent psychologically motivated and capable pharmacists from implementing an intended practice behaviour (Azjen, ; Doucette et al., ; Hopp, Sørensen, Herborg, & Roberts, ; Liaskou, White, Moss, Ratcliffe, & Cook, ; Luetsch, ; Roberts, Benrimoj, Chen, Williams, & Aslani, ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Reported behaviours related to managing patients and appropriate referral (secondary outcomes) further suggest ways that community pharmacy can improve access to treatment that extends beyond existing commissioned pharmacy‐based services such as minor ailments schemes. However, situational factors including work overload, conflicting workloads, lack of equipment and concerns over insurance were cited as barriers to transfer of training suggesting practice setting characteristics remain an obstacle to implementing behaviour change, confirming previously reported findings that a lack of perceived behavioural control / ability to engage in a behaviour in a practice environment may prevent psychologically motivated and capable pharmacists from implementing an intended practice behaviour (Azjen, ; Doucette et al., ; Hopp, Sørensen, Herborg, & Roberts, ; Liaskou, White, Moss, Ratcliffe, & Cook, ; Luetsch, ; Roberts, Benrimoj, Chen, Williams, & Aslani, ).…”
Section: Discussionsupporting
confidence: 77%
“…These barriers to implementation provide further evidence that changes to attitudes and behaviours alone are not enough for practice to change, and that a focus on the individual practitioner rather than on the structural, organisational context is a recognised shortcoming of studies that only consider psychological capacity and motivation. Moreover, while not explicitly investigated in this study, a lack of public or patient awareness of pharmacists’ clinical roles (Eades et al., ), as well as uncertainty regarding the numbers of patients presenting at community pharmacies requiring urgent care, together with reported lack of work‐based support for providing services outside reimbursed dispensing (Doucette et al., ; Hopp et al., ; Liaskou et al., ; Luetsch, ; Roberts et al., ) may limit opportunities to practise urgent care. Further roll out of this type of training would need to consider these patient, structural, organisational and contextual factors `and provide resources allowing for capacity building beyond the individual level to meet (as yet unforecasted) patient demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, low correlation coefficients from the multivariate regression indicate the presence of other unmeasured variables contributing to the variance in personality traits in this study. Finally, some state that the BFI may not be suitable for evaluating the personality traits of health professionals, claiming that the way it assesses the underlying facets of the trait of openness is not ideal for people whose curiosity might be technical or scientific, as opposed to artistic or aesthetic . The BFI is also primarily descriptive, it does not explain how personality traits develop .…”
Section: Discussionmentioning
confidence: 99%
“…One study found a relationship between empathy and conscientiousness and agreeableness, the latter of which is comprised of ‘forgiving’ and other traits . Another found pharmacists’ attitudes towards practice change to be associated with certain personality characteristics, such as ‘openness’, Need for achievement did not explain much of caring. While the results of this study provide a good baseline of understanding pharmaconomist caring behaviours, future studies could help determine additional factors associated with higher caring abilities and determine the extent to which different types of professional and educational interventions could positively affect caring behaviours.…”
Section: Discussionmentioning
confidence: 99%